Wittgenstein and justice - "Pitkin, Hanna Fenichel" (London, 1973)
This is an introduction for students of politics and society tot he later philosophy of Ludwig Wittgenstein, and some topics in "ordinary-language' philosophy. It argues that Wittgenstein's later philosophy offers a revolutionary new conception of language, and hence a new and deeper understanding of ourselves and the world of human institutions and action. Language is seen as activity, and words as signals, rather than labels for classes of objects.
Keywords: "Wittgenstein, Ludwing"